Gestione della Continuità Operativa delle Strutture Ospedaliere in Condizione di Maxi-emergenza - Boncinelli, Sergio; Masini, Emanuela; Mugnai, Laura (Proceedings e report, 2015)
This volume carries out a study with the aim to assess any flaw in the care, hospital and local services in the event of disasters with medium to long-term implications. The method features a set of indicators applied to three parameters (suitability, efficiency and quality of the health services). The project's aim is to identify the vulnerability of the hospitals in Florence in the event that the area of the Municipality and its surroundings are affected by a major emergency, with partial or complete damage to the continuity of care in hospitals. Furthermore, strategies and plans are proposed to maintain business continuity even in the event of such an emergency.